A Conceptual Framework for Integrated Economic–Environmental Modeling. (September 2016) - Banerjee, Onil; Cicowiez, Martin; Horridge, Mark; Vargas, Renato
Economy-wide models such as computable general equilibrium (CGE) models are powerful tools that provide insights on policy impacts on standard economic indicators. With the recent publication of the System of Environmental-Economic Accounting (SEEA), the power of this approach is amplified. This article addresses an important gap in economy-wide policy modeling applications and literature by developing a conceptual framework for the integration of the SEEA in the CGE framework, enabling for the first time the analysis of policy impacts on the economy and the environment in a quantitative, comprehensive, and consistent framework. Previous integrated modeling efforts have generally focused on the interaction between the economy and one environmental resource in isolation, requiring significant data reconciliation. Integration of SEEA into a CGE circumvents this resource intense process, enhancing analytical power, obviating the need for strong assumptions in reconciling economic–environmental data, reducing start-up costs, and increasing the timeliness of evidence-based policy advice.